PATIENT PROFILE NAVIGATED BY NURSES: TIME INTERVAL FOR START OF TREATMENT - Juliana Pompeu Pecoraro; Patricia dos Santos Claro Fuly (Universidade Federal do Paraná, 2024)
OBJECTIVE: Describe and analyze the sociodemographic and clinical profile and the interval between diagnosis and cancer treatment according to the gender of patients navigated by nurses in high complexity. METHOD: Observational, descriptive study conducted between December 2022 and September 2023, collected in October 2023, in an institutional database in supplementary health, including 119 patients navigated by nurses, in a pilot project carried out in Rio de Janeiro (Brazil). Descriptive and inferential statistics analyzed the data. RESULT:  There were 76 (63.87%) females; 77 (64.71%) over 60 years old; 60 (50.85%) with initial stage IV, p-value 0.077 for palliative treatment; treatment started after 60 days of diagnosis with similar percentages between genders, 30 women (39.47%) and 18 men (41.86%). CONCLUSION: Patient navigation by nurses reduces access barriers and improves care coordination, contributing to faster treatment initiation and better clinical outcomes in oncology practice.